Analysis of the Effect of External Counterpulsation Combined With High-Intensity Aerobic Exercise on Cardiopulmonary Function and Adverse Cardiovascular Events in Patients With Coronary Heart Disease After PCI - Zhao, Shiming; Liu, Shaowen; Wen, Yuan; Qi, Qiuhuan; Huang, Peng (Frontiers in Surgery, 2022)
Purpose: To explore the intervention effect of external counterpulsation (ECP) combined with high-intensity aerobic exercise (HIAT) on patients with coronary heart disease (CHD) after PCI. Methods: 124 patients with stable CHD after PCI admitted to our hospital from June 2018 to June 2021 were selected, and all patients were divided into control group and observation group using the random number table method. The control group received conventional treatment, The observation group received ECP combined with HIAT based on the control group. The cardiorespiratory function indexes, exercise endurance indexes, incidence of main adverse cardiovascular events (MACE), Barthel index of the two groups were observed. Results: After intervention, METs max, VO2 max, VO2 max/kg, VO2 max/HR, and PP, ED, AT, and Barthel score in both groups were significantly higher than before intervention, and patients in the observation group were significantly higher than those in the control group (P<0.05). The incidence of MACE in the observation group (3.23%) was lower than in the control group (12.90%) (P<0.05). Conclusion: ECP combined with HIAT can improve the cardiopulmonary function of patients with CHD after PCI, and improve exercise endurance, reduce the incidence of MACE, improve patients' ability of daily living.